2014
DOI: 10.3724/sp.j.1009.2013.00391
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effect of new constituents from the hooks of Uncaria rhynchophylla on scopolamine-induced memory impairment

Abstract: Compound 1 exhibited a better memory enhancing effect than tacrine, a positive agent, at the same dose in the passive avoidance test and a similar property in the water-maze test, and its action may be mediated, in part, by the acetylcholine enhancing cholinergic nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Each rat was allowed to search for the hidden platform for 90 s and those who failed to locate the platform were gently guided and placed on the platform for 10 s. Animals of all groups underwent 3 training trials/day for 6 consecutive days. On the 7 th day, animals received a probe trial (retention test), in which the platform was removed from the tank, and the latency to locate the position of the platform within the period of the test (60 s) and the time spent on the target quadrant were recorded [40].…”
Section: Morris Water Maze (Mwm)mentioning
confidence: 99%
“…Each rat was allowed to search for the hidden platform for 90 s and those who failed to locate the platform were gently guided and placed on the platform for 10 s. Animals of all groups underwent 3 training trials/day for 6 consecutive days. On the 7 th day, animals received a probe trial (retention test), in which the platform was removed from the tank, and the latency to locate the position of the platform within the period of the test (60 s) and the time spent on the target quadrant were recorded [40].…”
Section: Morris Water Maze (Mwm)mentioning
confidence: 99%
“…Modern pharmacological studies have Mechanism of the protective effects of the combined treatment with rhynchophylla total alkaloids and sinapine thiocyanate against a prothrombotic state caused by vascular endothelial cell inflammatory damage demonstrated that RTA exerts a variety of pharmacological effects, including reducing blood pressure and anti-arrhythmia, protecting against cerebral hypoxia and ischemia, inhibiting platelet aggregation and thrombosis, improving vascular remodeling, antagonizing the senescence of vascular endothelial cells (VECs), as well as sedative and antiepileptic effects on the central nervous system (4)(5)(6). Raphani semen is the dried ripe seed of Raphanus sativus L. Recent studies have shown that Raphani semen exhibits a strong antihypertensive effect and its active component is sinapine thiocyanate (7).…”
Section: Introductionmentioning
confidence: 99%
“…The present study is the first to demonstrate that trans -anethole facilitates normal hippocampal NMDA receptor-dependent and -independent LTP induction. Trans -anethole was previously reported to enhance memory capacity in behavioral tasks [ 8 ]. Consistent with our results presented in Figure 5 , previous reports indicated that TMT can induce neurotoxicity, loss of neuronal cells, and impairments of hippocampal learning and memory assessed using different methods [ 12 , 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that trans -anethole has anti-inflammation, anticonvulsant, antinociceptive, and anticancer capacities [ 4 , 5 , 6 , 7 ]. Trans -anethole was also reported to have an anti-amnesic effect in behavioral tasks [ 8 ] and to exert a neuroprotective effect in cortical neuronal cells [ 9 ]. However, the potential effects of trans -anethole are not fully understood and its action mechanism(s) in the nervous system have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation